Brainstorming Effect in Pregnant Women on Knowledge of Childbirth Planning and Complications Prevention Programs - Galuh Andika; Sri Wahyuningsih; Agustina Widayati (Health and Technology Journal (HTechJ), 2023)
The birth planning and complication prevention program (P4K) is an effort from the government to reduce maternal mortality (MMR). To support these efforts, learning needs to be provided; brainstorming provides a structured format that can increase the quantity and quality of responses from the participants. The brainstorming method effectively delivers information according to the mother's characteristics. However, the effect of health education on the brainstorming method for pregnant women on the P4K is still not explained. This study aims to explain the impact of brainstorming on pregnant women on knowledge of P4K in Kertosari Village, Lumajang Regency. The design of this research is a Quasy Experiment with a pre-post design. The sample in this study was 30 pregnant women who were taken using total sampling. This research was conducted in Kertosari Village, Pasrujambe District, Lumajang Regency. This research concludes that there is an effect of brainstorming on the knowledge of pregnant women about the Birth Planning and Complications Prevention (P4K) Program in Kertosari Village, Lumajang Regency, with (ρ=0.000<0.05). It is hoped that Brainstorming can be used as an alternative in providing health education to pregnant women in promotive and preventive efforts in the success of the Childbirth Planning and Complications Prevention Program (P4K).